Spinodal decomposition of a confined colloid-polymer system. - Jamie, E; Dullens, R; Aarts, D (2012)
We study the demixing via spinodal decomposition of a fluid-fluid phase separating colloid-polymer mixture confined between parallel plates, where one of the phases completely wets both walls. Using confocal scanning laser microscopy, we are able to obtain real space images, both parallel and perpendicular to the cell walls. We observe three distinct morphologies: the formation of a bicontinuous network, which coarsens into cylindrical tubes bridging the plates, and finally develops into a network structure in two dimensions. Through image analysis of the system as a whole, and the tracking of individual domains, we are able to perform a detailed study of the mechanisms of phase coarsening at each stage. We are able to directly test the condition for which bridges connecting both confining walls do not sever. Finally, we consider the role of hydrodynamics and of thermal interface fluctuations in our system.